Evaluation and Comparison of Mucormycosis Patients' Features Undergoing Functional Endoscopic Sinus Surgery Prior to and during the COVID-19 Pandemic: A Case-Control Study. (7th June 2022) - Dehghanpisheh, Laleh; Eghbal, Mohammadhossein; Salari, Mehrdad; Shahriarirad, Reza; Borzou, Niloofar; Vatankhah, Pooya
Abstract : Background . Rhinocerebral mucormycosis is a serious invasive fungal infection that is one of the most aggressive and lethal of invasive mycoses. The coronavirus disease (COVID-19) has been linked to immune dysregulation, and patients with COVID-19 have been reported to be at risk for developing invasive fungal infections. This study is conducted to evaluate the concurrence of mucormycosis among COVID-19 patients. Methods . In this retrospective, cross-sectional study, hospital records of patients with mucormycosis, as well as COVID-19 admitted to Khalili Hospital, as the major referral center for functional endoscopic sinus surgery (FESS) in southern Iran, were collected. Demographic and clinical information was extracted and subsequently analyzed. Results . Among 59 mucormycosis patients undergoing FESS, 41 (69.5%) were during the COVID-19 pandemic, while 18 (30.5%) were during one year before the COVID-19 pandemic. The average age was 49.33 ± 20.52, and 64.4% had diabetes mellitus, while 62.7% had COVID-19. The most common presentation was periorbital edema (56.9%), followed by necrotic tissue (48.3%). Although the total number of cases increased during the COVID-19 period compared to the case before the pandemic, the overall pattern and features of the patients had no significant difference, except regarding a significant increase in the presentation of necrotic tissue and also the use of corticosteroids. Most cases developed mucormycosis two weeks after COVID-19. The overall mortality was 36.8%, which is not statistically associated with COVID-19. Conclusion . Even in the absence of comorbidities, physicians should be aware of the risk of secondary fungal infections in patients with COVID-19 who were treated with corticosteroids.